Preparation and characterization of calcium-doped graphene oxide-chitosan Nanocarrier to enhance the gene delivery in MCF-7 cell line - Amirreza Diari Bidgoli; Abbas Farmany; Mohammad Taheri; Meysam Soleimani; Fatemeh Nouri (Scientific Reports)
Abstract Gene delivery has emerged as a novel and effective method in the treatment of malignancies within medical interventions by applying nanotechnology. Consequently, the development of appropriate nanocarriers is a key focus of this research. Dynamic light scattering (DLS), fourier transform infrared (FT-IR) spectroscopy, x-ray diffraction (XRD), and thermal gravimetric analysis (TGA) were employed for the characterization of the synthesized nanocarrier. Furthermore, to assess the gene transfer capability of the nanocarrier, various techniques such as gel retardation assay, nuclease resistance assay, cytotoxicity assay, flow cytometry, and transfection were employed. The average particle size and zeta potential of the GO-CS@Ca nanocarrier were obtained as 319.8 nm and + 92.8 mv, respectively. In the gel retardation test, it was observed that pDNA was effectively condensed by the GO-CS@Ca nanocarrier. The results of the MTT assay indicated that both GO-CS@Ca nanocarrier and the GO-CS@Ca/pDNA nanoplex with low toxicity. In flow cytometry analysis, it was observed that the complexation of pDNA with the GO-CS@Ca nanocarrier resulted in effective gene delivery to the MCF-7 cell line and consequently increased apoptosis induction.